Analisis SWOT sebagai Dasar Strategi Pemasaran Kedai Kopi Peh Corner - Petty Arisanti (JUDICIOUS, 2021)
Marketing is a social and management process that is carried out optimally by utilizing company resources to achieve large sales of goods or services and provide sales benefits oriented to customer satisfaction. Indirect marketing to minimize losses and threats to the company. This study aims to determine the strengths, weaknesses, opportunities and threats for the company. The research method used is qualitative research with an empirical approach in the form of information from research results. The data analysis technique used is data reduction, data presentation and drawing conclusions from the data. Based on the results of research with SWOT analysis shows that the company is in an unfavorable condition where there are many weaknesses and threats. For this reason, companies should switch to using a concentrated strategy to minimize costs.